Nutritional Profile and Antioxidant Properties of Hemp (Cannabis sativa L.) Seed from Romania - Doris Floareș Oarga; Adina Berbecea; Diana Obiștioiu; Anca Hulea; Ionela Hotea; Ciprian Buzna; Luana Alexandra Sabo; Anca Ofelia Panda; Isidora Radulov (Applied Sciences, 2025)
This study evaluates the nutritional and phytochemical properties of six industrial hemp varieties from Romania. The proximate composition (proteins, lipids, ash, moisture, fiber, and carbohydrates), total polyphenol content (TPC), total flavonoid content (TFC), antioxidant activity (DPPH), and macro/microelements were analyzed. Two extraction methods were used: conventional and ultrasound-assisted extraction. The results showed a protein content of 20.92–25.39 g/100 g, lipid content 24.92–28.43 g/100 g, fiber 25.92–31.21 g/100 g, ash 4.71–6.38 g/100 g, moisture content 4.84–5.96 g/100 g, carbohydrates between 35.05 and 43.58 g/100 g, and energy value between 483.25 and 502.40 kcal/100 g. The TPC content varied between 732.36 and 1457.60 mgGAE/kg for conventional extraction methods and from 1003.48 to 1519.87 mg GAE/kg for ultrasound-assisted methods. The TFC content was 343.91–1013.40 mg QE/kg for conventional extraction methods and 511.92 to 1222.14 mg QE/kg for ultrasound-assisted methods. The results showed that the extraction method influenced the phytochemical compounds. Macroelements were dominated by potassium (5533.23 μg/g), magnesium (2616.34 μg/g), and calcium (1853.51 μg/g). Microelements showed the highest levels of iron (189.49 μg/g), followed by manganese (138.26 μg/g), zinc (75.25 μg/g), and copper (13.08 μg/g). Nickel and cadmium were found in trace amounts. Multivariate analysis (PCA) was used to correlate the data.